Poslání a aktuální problémy předškolního vzdělávání - postoje a názory ředitelek mateřských škol - Jaroslava Simonová; Eva Potužníková; Jana Straková (Karolinum Press, 2018)
The introduction of compulsory pre-school attendance as a means to improve readiness for school, especially among disadvantaged children, has raised a series of controversies in the Czech Republic. Relatively little attention has been paid to the opinions and attitudes of an important group of actors in this important change − kindergarten teachers. The aim of this empirical study is to present the results of a research study focused on the views of kindergarten principals on the mission and current problems of preschool education. The principals of 383 kindergartens selected in two-stage stratified random sampling responded to a questionnaire. Their answers to closed-ended questions were analysed by descriptive statistical methods, while open-ended questions were analysed using qualitative content analysis. Almost all the kindergarten principals do not consider readiness for school to be the primary target of preschool education; two-thirds of them do not see reducing differences between children from different socioeconomic backgrounds as a priority. The biggest problems are seen as lying in the administrative burden, low capacities of kindergartens, funding, and problems with parents and children. The principals noticed significant changes in children's readiness for kindergarten, a lack of social skills, and the prevalence of diagnosed disorders. These results are discussed with regard to educational policy measures which have recently been proposed and introduced.